The German historicist tradition - Beiser, Frederick C., 1949- (Oxford : Oxford University Press, 2011)
This is the first history in English of German historicism, the intellectual tradition which holds that history is the key to understanding all human values, beliefs and actions. Beiser surveys the key thinkers from the mid-18th to the early 20th century and illuminates the sources and reasons for this revolution in modern thought.
Also issued in print format.
Description based on online resource; title from PDF title page (viewed on Jan. 21, 2012).
Includes bibliographical references and index.
Keywords: Historicism; Philosophy, German -- 19th century